THE IMPLEMENTATION OF EARLY DETECTION AND PREVENTION IN THE PREVENTION OF RADICALISM BY THE NATIONAL AND POLITICAL UNITY AGENCY IN CIMAHI CITY, WEST JAVA PROVINCE - Handayani, Alfina; Wiredarme, Wiredarme (Fakultas Hukum Tata Pemerintahan, 2024)
The author's interest is in acquiring the title due to the discovery of a Khilafatul Muslimin group in Cimahi City that has been actively disseminating radical beliefs since the 2000s. In contrast, Cimahi metropolis, known as the Army City, can be presumed to be a secure metropolis free from radicalism. The objective of this study is to assess the effectiveness of early identification and preventative measures in mitigating the spread of extremism. Furthermore, it is crucial to identify the barriers that develop during the implementation of early detection and prevention, as well as the measures taken by the Cimahi City National and Political Unity Agency to address these hurdles. The research employed a qualitative descriptive methodology, utilizing an inductive technique. The data sources utilized in this study encompass both primary and secondary data sources. The employed data analysis procedures encompass data reduction, data display, and data verification. Common methods of data collection are interviews, observations, and documentation. According to the findings from interviews, field observations, and documentation collecting, the current implementation of early detection and prevention measures to combat extremism in Cimahi City has not been effective due to a lack of intelligence expertise. The current challenges encompass the scarcity of skilled personnel and constrained financial resources to facilitate the execution of early identification and prevention measures. Efforts to address current challenges including incorporating members into intelligence science education and training programs, as well as enhancing supervision in the community settings that are exposed to extremism. To implement early detection and prevention effectively, it is necessary to enhance the directing function by assigning competent individuals to vacant positions and providing them with additional education and training in the field of intelligence science. Furthermore, close coordination with the Cimahi City Regional Leadership Coordination Forum is essential to facilitate the deradicalization program.